2010
DOI: 10.3109/17435390.2010.537382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticle surface coating on bioaccumulation and reproductive toxicity in earthworms (Eisenia fetida)

Abstract: The purpose of this study was to investigate the effect of surface coating on the toxicity of silver nanoparticles (Ag NPs) soil. Earthworms (Eisenia fetida) were exposed to AgNO(3) and Ag NPs with similar size ranges coated with either polyvinylpyrrolidone (hydrophilic) or oleic acid (amphiphilic) during a standard sub-chronic reproduction toxicity test. No significant effects on growth or mortality were observed within any of the test treatments. Significant decreases in reproduction were seen in earthworms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(129 citation statements)
references
References 40 publications
11
116
1
1
Order By: Relevance
“…Schlich et al (2013) showed slightly higher bioaccumulation factors (BAF) in earthworms exposed to Ag NPs, although the free Ag ion concentration in the soil was comparable for both Ag forms. Shoults-Wilson et al (2011) found a lower BAF for Ag NP exposure, however, Ag bioaccumulation was not related only to Ag ions released from the nanoparticles. Up-to-date, only one study on the kinetics of Ag NPs in the springtail Folsomia candida is available in the literature (Waalewijn-Kool et al, 2014).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Schlich et al (2013) showed slightly higher bioaccumulation factors (BAF) in earthworms exposed to Ag NPs, although the free Ag ion concentration in the soil was comparable for both Ag forms. Shoults-Wilson et al (2011) found a lower BAF for Ag NP exposure, however, Ag bioaccumulation was not related only to Ag ions released from the nanoparticles. Up-to-date, only one study on the kinetics of Ag NPs in the springtail Folsomia candida is available in the literature (Waalewijn-Kool et al, 2014).…”
Section: Introductionmentioning
confidence: 73%
“…The bioaccumulation of Ag NPs and ionic Ag (from AgNO3) has been evaluated in the earthworm Eisenia fetida after 28 days of exposure (Schlich et al, 2013;Shoults-Wilson et al, 2011). Schlich et al (2013) showed slightly higher bioaccumulation factors (BAF) in earthworms exposed to Ag NPs, although the free Ag ion concentration in the soil was comparable for both Ag forms.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nitrate had greater reproductive toxicity than NPs for E. fetida, although no significant differences were found for effects on growth and survival [85]. Not only did the endpoint analyzed have great influence on the toxicity of NPs and metal salts, but the exposure time did as well.…”
Section: Silvermentioning
confidence: 85%
“…However, extended X-ray absorption fine structure spectroscopy analysis in soil showed that Ag in earthworms exposed to Ag NPs suggests that accumulation was not caused only by the ionic form (i.e., ions dissolved from NPs), but that nondissolved particles contributed to Ag accumulation in the organisms [85].…”
Section: Silvermentioning
confidence: 99%
“…The physical properties of these particles have been previously described. 35,41 Briefly, the particles were polydisperse with particle sizes ranging from 30 to 80 nm, and with aggregates of up to 200 nm in diameter based on TEM and DLS measurements (z-average hydrodynamic diameter). The initial Ag(0) content as determined by X-ray absorption spectroscopy was 80−85 wt % with the balance being an oxidized form of Ag, either Ag 2 O or a mixture of Ag 2 O and Ag 2 S. X-ray diffraction (XRD) confirmed the presence of predominantly crystalline Ag(0).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%